2006
DOI: 10.1038/sj.jes.7500482
|View full text |Cite
|
Sign up to set email alerts
|

Variation of biocontaminant levels within and between homes — the AIRALLERG study

Abstract: Few epidemiological studies report on reliability of exposure measurements even though this significantly influences the results of correlation and regression analysis often used in these studies. Poor reliability of exposure measurement reduces the ability to detect a true association between a certain component and health outcome variables. The aim of this study was to determine the ratio of the within-home and between-home components of variance of a number of biocontaminants measured in house dust in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
(28 reference statements)
4
17
0
Order By: Relevance
“…The within-home variation was low for indoor and negligible for outdoor air. The above findings are similar to those reported for beta-glucan measured in dust: Chew et al (2001) found comparable within-home and between-home variations, and Giovannangelo et al (2007) reported within-home variances to be close to or less than the betweenhome variances. For all sources of indoor and outdoor within-home variation, none was due to day-to-day variances.…”
Section: (1?3)-b-d-glucansupporting
confidence: 92%
See 1 more Smart Citation
“…The within-home variation was low for indoor and negligible for outdoor air. The above findings are similar to those reported for beta-glucan measured in dust: Chew et al (2001) found comparable within-home and between-home variations, and Giovannangelo et al (2007) reported within-home variances to be close to or less than the betweenhome variances. For all sources of indoor and outdoor within-home variation, none was due to day-to-day variances.…”
Section: (1?3)-b-d-glucansupporting
confidence: 92%
“…Chew et al (2001) analyzed beta-glucan in dust samples collected in 23 Dutch homes over a period of a year and found similar variation of its levels within and between homes. Giovannangelo et al (2007) analyzed the variance in the levels of beta-glucan, endotoxin, extracellular polysaccharide, and indoor allergens in duplicate house dust samples collected in 61 homes. They found that the within-home variance was less than half of the between-home variance in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Dust samples of a single time-point cannot represent the overall exposure, as the microbial components in house dust samples may change over time. A previous AirAllerg investigation showed that the within-home variance of endotoxin, (1,3)-b-D-glucan and EPS measurements was small compared with the between-home variance [34]. However, some investigations looked at variations over time and performed repeatability analyses within and between homes.…”
Section: Discussionmentioning
confidence: 99%
“…These include the ECRHS-I and II (FP3, FP4 and FP5) (38,139), AIRALLERG (Effects of outdoor and indoor air pollution on the development of allergic disease in children, FP5) (140,141), Health effects of particles from motor engine exhaust and ambient air pollution, FP5 (142), PATY (Pollution and the young combined analyses of cross-sectional studies of respiratory health of children and air pollution, FP5) (143)(144)(145) and Respiratory Allergy and Inflammation due to Air Pollution (FP5) (146). BioAir (FP5), a longitudinal assessment of clinical course and biomarkers in severe chronic airway disease, has used modern clinical measurements and the exploitation of new molecular methods to define biomarkers of chronic airway inflammation and remodeling.…”
Section: How Eu Projects Can Helpmentioning
confidence: 99%